2016
DOI: 10.18203/2349-2902.isj20164451
|View full text |Cite
|
Sign up to set email alerts
|

Study of clinical profile and outcome of gall bladder perforations at a tertiary care centre from central India

Abstract: INTRODUCTIONAmongst the diseases of the gall bladder calculous cholecystitis is the most common. Acute cholecystitis can get complicated and result in complications like empyema, gall stone ileus, cholecystoenteric fistula, emphysematous cholecystitis, gall bladder perforation and biliary peritonitis.1 Of these, gall bladder perforation (GBP) is an uncommon but life-threatening complication of acute cholecystitis, with a reported mortality rate of 12-42%. [2][3][4] Niemeier in 1934 has classified gall bladder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In similar studies conducted by Derici H et al, and Jain S et al, type II was found to be more common followed by type I. 6,7 This is in contrary to the study done by Nandyala VN et al, in which type I was more common than type II. 4 On clinical examination, most of the patients with type II GBP had guarding present in the right hypochondrium (n=4/7) and an USG finding of pericholecystic collection (n=6/7), whereas patients with type I GBP had diffuse guarding (n=3/5) and free fluid in the peritoneal cavity on USG (n=4/5).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In similar studies conducted by Derici H et al, and Jain S et al, type II was found to be more common followed by type I. 6,7 This is in contrary to the study done by Nandyala VN et al, in which type I was more common than type II. 4 On clinical examination, most of the patients with type II GBP had guarding present in the right hypochondrium (n=4/7) and an USG finding of pericholecystic collection (n=6/7), whereas patients with type I GBP had diffuse guarding (n=3/5) and free fluid in the peritoneal cavity on USG (n=4/5).…”
Section: Discussionmentioning
confidence: 71%
“…This is in agreement with various other similar studies. 4,6,7 The incidence of type II and type I GBP was found to be 58.3% and 41.6% respectively. Author did not come across any type III GBP during the study period.…”
Section: Discussionmentioning
confidence: 94%